Online synchronous inspection and system optimization of flexible food packaging bags by using machine vision and sensing technique - Lizhi Gu; Qiong Li; Ehui Huang; Mingrui Li; Shanping Gao; Kin Sam Yen; Shuting Li; Junqin Zhou; Zhenjie Chen (Universitas Ahmad Dahlan, 2023)
Flexible food packaging in the market is increasingly favored, and its quality is essential and indispensable for safety and convenience. However, quality inspection still stays in the manual stage, or partially manual inspection remains, in production, leading low efficiency, lack and even false inspection, hardly meeting the requirements of the modern output. This paper proposes and optimizes the design of an automatic detection system with intelligence for flexible food packaging bag, which can effectively be adopted to check the quality of packaging trademark patterns, fillers, and sealing quality. The inspection system runs with two-stage structure, machine vision, pressure sensing and synchronization to improve efficiency and ensure the normal production beat. Simplex Method is adopted to determine the best synchronous speeds online to achieve the best expectation. Comparison has been made between the manual inspection and our automatic operation, the sample of 10000 was statistically analyzed and results have shown that two workers were saved and the correctness rate of inspection raised up to 999.8‰.